Valerie Shirreff Memorial Lecture Politics and Power: Nursing in Canada - Pépin, Lucie (Operating Room Nurses Association of Canada Journal, 1999)
Speaking about issues that are of great concern to us all, brings me back to my roots. It brings me back to the people and the profession which first sparked my passion for service, for change and for public action.